The Effect Ease Of Use And Perceived Risk On Purchasing Decisions On Marketplace Shopee - Wicaksono, Dimas Setiawan; Ruhamak, Muhammad Dian; Yap, Nonni (Trunojoyo University of Madura, 2023)
The purpose of this study is to determine the effect ease of use and Perceived risk on purchasing decisions on marketplace shopee in kediri city. This research is of the explanatory research type with a quantitative approach. The population of the study consists of Shopee marketplace users in Kediri city, and the exact population size is unknown. The sampling technique used in this study is non-probability sampling with purposive sampling technique. The sample size in this study is 100 respondents, determined using the Lemeshow formula. Data analysis is conducted using multiple linear regression or descriptive statistics. Data processing in this study is performed using SPSS version 23. The results of this study show that: (1) Ease of use has a partial significant positive effect on purchasing decisionss with a significance value of 0.000 0.05. (2) Perceived risk also has a partial significant negative effect on purchasing decisionss with a significance value of 0.002 0.05. (3) Simultaneously, ease of use and Perceived risk have a significant influence on purchasing decisionss, with a calculated F count of 19.831 the F table value of 2.69, and the obtained significance value is 0.00 α 0.05.